The Legal and Economic Implications of Electronic Discovery Options for Future Research - Dertouzos, James N. (RAND Corporation, 2008)
The growing volume of electronically stored information has led to concerns that requests for electronic discovery (e-discovery) can increase litigation costs, impose new risks on lawyers and their clients, and alter expectations about likely court outcomes. The authors provide an overview of the issues involved and outline five avenues for future research on the legal and economic implications of e-discovery.